2019
DOI: 10.1186/s12889-019-6942-7
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all: HIV prevalence and correlates of risk for men who have sex with men, transgender women in multiple cities in Papua New Guinea

Abstract: Background Biobehavioral data about men who have sex with men (MSM) and transgender women (TGW) in Papua New Guinea (PNG) are limited to those who sell sex. Information about those MSM and TGW who do not sell sex is necessary to guide HIV prevention and treatment efforts. Methods We conducted respondent-driven sampling (RDS) surveys among MSM and TGW in Port Moresby, Lae, and Mt. Hagen, PNG from in 2016 and 2017. Eligibility criteria was: aged > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Hagen. Details of the population socio-demographics and characteristics can be found in the article by Kelly-Hanku et al [ 20 ] and Hakim et al [ 19 ] for FSW and MSM and TGW population, respectively. All data reported below are weighted estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Hagen. Details of the population socio-demographics and characteristics can be found in the article by Kelly-Hanku et al [ 20 ] and Hakim et al [ 19 ] for FSW and MSM and TGW population, respectively. All data reported below are weighted estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Population sub-group sizes and their numbers of partners Group (15–49 years) Share of Population Married/with stable heterosexual partner Partners/year Sex acts/partner/year Source Not yet sexually active Women 14% NA 0 NA Demographic and Health Surveys (DHS) 2006 ( National Statistics Office of Papua New Guinea, 2009 ) and 2016–2018 ( National Statistics Office of Papua New Guinea, 2019 ) Low-Risk Women 51% 100% 1 100 DHS, community surveys ( Maibani-Michie et al., 2011 ; National AIDS Council Secretariat, 2012 ), studies in sexual health clinics ( Vallely et al., 2014 ) and model’s balancing of stable & casual partnerships between women and men Medium-Risk Women 33% 30% 3 casual 30 High-Risk Women/FSW 2.3% 12% 55 clients 5 National size estimations ( Hakim et al., 2019 ; Kelly-Hanku et al., 2018 ; Weikum et al., 2019 ); IBBS ( Hakim et al., 2019 ; Kelly-Hanku et al., 2018 , 2020 ; Millan et al., 2007 ); studies ( Family Health InternationalUSAID AsiaPapua New Guinea National AIDS Council, 2011 ; Maibani-Michie & Yeka, 2005 ; Maibani-Michie et al., 2007 ; Morineau, 2011 ; National AIDS Council Secretariat, 2012 ; Papua New Guinea National AIDS Council SecretariatPartners, 2008 ; Yeka et al., 2006 ), 2018 national HIV investment case ( National AIDS Council Papua New GuineaAustralian Governme...…”
Section: Methodsmentioning
confidence: 99%
“…bisexual) 5 13 National size estimations ( Weikum et al., 2019 ); IBBS ( Hakim et al., 2019 ; Kelly-Hanku et al., 2018 ; Millan et al., 2007 ); studies ( Family Health InternationalUSAID AsiaPapua New Guinea National AIDS Council, 2011 ; Maibani-Michie & Yeka, 2005 ; Maibani-Michie et al., 2007 ; Morineau, 2011 ; National AIDS Council Secretariat, 2012 ; Papua New Guinea National AIDS Council SecretariatPartners, 2008 ; Yeka et al., 2006 ), 2018 national HIV investment case ( National AIDS Council Papua New GuineaAustralian Government Department of Foreign Aid and TradeUNAIDS, 2018 ) All men 100% 2019 World Population Prospects, 2015–2030 medium variant projections ( United Nations Population Division, 2019 ) b. Syphilis intervention coverages historically, currently and as targeted in alternative program scale-up scenarios Population group Historic Current & Constant-coverage, 2020+ Single-intervention scale-up, 2023+ Scale-up: Moderate Scale-up: Maximum Source or estimation method 1985 2023+ all interventions combined Clinical treatment of symptomatic Primary/Secondary episodes Low- & Medium-risk Women 25% 25% 55%, 60% & 60% (as 1 scenario) 35% 40% WHO global STI estimations assume 35% for countries with low treatment access; ( Newman et al., 2015 ; Rowley et al., 2019 ) Authors consider PNG to be among the very lowest-treatment access countries, evidenced by low self-reported use by key populations to any HIV/STI prevention and treatment services ( Family Health InternationalUSAID AsiaPapua New Guinea National AIDS Council, 2011 ; Hakim et al., 2019 ; …”
Section: Methodsmentioning
confidence: 99%
“…For MSM and TGW, participants had to be born a biological male, to be aged �12 years, have had oral or anal sex with another man within the past 6 months, to speak English or Tok Pisin (Melanesian pidgin), and to have a valid study coupon. For a more detailed discussion on the RDS method as it was used in this study see Hakim et al [9]. For further details on issues with the eligibility age and waiver of parental / guardian consent see Ethics below.…”
Section: Methodsmentioning
confidence: 99%
“…For example, our recent key population biobehavioral survey (BBS) in Papua New Guinea, called Kauntim mi tu (translation, 'Count me too') (June 2016 -December 2017), showed that HIV infection rates among FSW are 11 to 19 times higher than among other adults [7,8]. The estimated infection rates for MSM/TGW are 7 to 8 times higher than for other adults [7,9].…”
Section: Introductionmentioning
confidence: 99%